2022
DOI: 10.1021/acsomega.2c01879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Viscosity and the Solution Gas–Oil Ratio on Foamy Oil Flow in Solution Gas Drive

Abstract: The anomalously high recovery of solution gas drive in some heavy oil reservoirs has been associated with foamy oil. The effects of external factors such as temperature, permeability, and the pressure depletion rate on foamy oil flow have been studied sufficiently, but few studies are available on the effect of heavy oil itself. In order to investigate the effect of oil viscosity and the solution gas–oil ratio on foamy oil, 11 tests of solution gas drive through a sandpack were carried out in this work. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Regarding the stability of oily foam, previous studies have indicated that it is primarily assessed through measurements of foam half-life (the time it takes for a foam’s volume to reduce to half of its initial volume after formation) and maximum foam volume. Factors such as bubble radius, bubble morphology, foam comprehensive index, and others have not been explored. Therefore, there is a need for a comprehensive evaluation method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the stability of oily foam, previous studies have indicated that it is primarily assessed through measurements of foam half-life (the time it takes for a foam’s volume to reduce to half of its initial volume after formation) and maximum foam volume. Factors such as bubble radius, bubble morphology, foam comprehensive index, and others have not been explored. Therefore, there is a need for a comprehensive evaluation method.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of enhancing heavy crude oil recovery with oily foam is akin to gas dissolution drive. 7 It involves gas dissolving into crude oil, leading to volume expansion, reduced density, improved flow, increased relative permeability, and elevated reservoir pressure. These factors collectively enhance heavy crude oil recovery by improving flow and mobility, making it easier to extract the oil from the reservoirs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation